Study of Irisin in End Stage Renal Disease on Hemodialysis - Ahmed Ali, Abdullah; Shafeeq, Noorhan K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Irisin is a myokine that controls energy metabolism by making adipose tissue brown. The present goal in doing this research was to determine how irisin concentration relates to other biochemical markers of disease. Hemodialysis (HD) for chronic kidney failure. The study included 30 individuals with end-stage renal disease on HD and 30 healthy subjects as the control group. The ages of all patients and the control group ranged from (25 to 60) years. The excluded criteria included patients with viral hepatitis and diabetes. Serum irisin concentration and the level of fasting serum glucose (FSG), urea, creatinine (Cr), total protein (TP), albumin (Alb), albumin to creatinine ratio (ACR), total cholesterol (TC), alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), sodium (Na+), potassium (K+), calcium (Ca+2), phosphorus (PO4), and vitamin D were measured. The results showed significantly reduced serum irisin, vitamin D, Na+, K+, Ca+2, PO4, TC, ALT, AST, glomerular filtration rate (eGFR), total protein TP, Alb, ACR, weight, height, and a significantly increased level of urea, Cr, and ALP. in patients compared with the control group. Also, the results showed significant negative correlations between irisin and age, weight, height, FSG, Alb, urea, AST, ALP , ALT, Na, and vitamin D in the HD group. While significant positive correlations were found between irisin and body mass index (Cr, Ca, Po4, Tp, TC, and K),  as well as significant negative correlations between vitamin D and weight (hight, BMI, FSG, Cr, Ca, PO4, TP, Alb, urea, ALP, ALT, and Na), While significant positive correlations were found between vitamin D age, AST, and K, In conclude, it has been found that serum irisin levels and vitamin D levels both fell considerably in uremic patients receiving frequent HD. Irisin has a perfect cut-off value of 78% sensitivity and 99.9% specificity, according to a ROC analysis, suggesting it is a reliable diagnostic marker.